Pijat Oksitosin terhadap Produksi Asi pada Ibu Post Partum - Reni Fitria; Nia Retmiyanti (Universitas Batanghari Jambi, 2021)
Insufficient milk production is often a problem for postpartum mothers. Likewise, what is experienced by post partum mothers in the Puskesmas S work area, such as nipple blisters, crying babies, and decreased baby weight. The purpose of this study was to determine the effect of oxytocin massage on milk production in post partum mothers. This research method is one group pre test post test design. The population in this study were 33 post-partum mothers, a sample of 33 post-partum mothers with a total sampling technique, using the T-test. a number of 0 (0%), quite fluent a number of 7 postpartum mothers (21.2%), less fluent a number of 26 postpartum mothers (78.8%), after the oxytocin massage most of the respondents. The release of ASI was smooth as many as 33 postpartum mothers (100%). The T-test showed that the value of p = o, ooo <a (0.05) which indicates that there is an effect of oxytocin massage on the smoothness of breast milk. This shows the need for oxytocin massage so that it can help accelerate breastfeeding in nursing mothers.